2021
DOI: 10.1111/birt.12549
|View full text |Cite
|
Sign up to set email alerts
|

Experience predicts the duration of exclusive breastfeeding: The serial mediating roles of attitude and self‐efficacy

Abstract: Background and aims The relationship between prior breastfeeding experience and the duration of exclusive breastfeeding is of significant interest, but few studies have explored the mechanisms underlying this relationship. The purpose of this study is to address two hypotheses: (a) that attitude and self‐efficacy mediate the relationship between previous breastfeeding experience and the duration of exclusive breastfeeding; and (b) that attitude and self‐efficacy have serial mediation functions in this relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a study that examined the breastfeeding attitudes of 394 mothers in a hospital using the IIFAS and followed the exclusive breastfeeding behavior for six months postpartum, found that attitude played the important role in duration of exclusive breastfeeding. Improving breastfeeding attitudes in women without breastfeeding experience can promote the duration of exclusive breastfeeding [ 43 ]. A Malaysian study used the IIFAS to investigate paternal breastfeeding support and attitudes and maternal breastfeeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that examined the breastfeeding attitudes of 394 mothers in a hospital using the IIFAS and followed the exclusive breastfeeding behavior for six months postpartum, found that attitude played the important role in duration of exclusive breastfeeding. Improving breastfeeding attitudes in women without breastfeeding experience can promote the duration of exclusive breastfeeding [ 43 ]. A Malaysian study used the IIFAS to investigate paternal breastfeeding support and attitudes and maternal breastfeeding practices.…”
Section: Discussionmentioning
confidence: 99%
“…The American Academy of Pediatrics [ 11 ] (AAP), the American College of Obstetricians and Gynecolo gists (ACOG), Professional organizations such as and the [ 12 ] consider breast milk to be the nutritional standard for infant feeding.The World Health Organization (WHO) recommends that exclusive breastfeeding (EBF) should continue until 6 months, followed by gradual addition of complementary foods until 24 months [ 13 ]. Infant feeding attitude is an important predictor of infant feeding decisions, which plays a decisive role in compliance with infant feeding guidelines [ 14 , 15 ], and is also a predictor of breastfeeding duration and exclusivity [ 16 ]. A spouse’s attitude towards breastfeeding also influences a mother’s decision to breastfeed and is associated with the initiation and duration of breastfeeding [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, due to the limited sample size, this study addresses only the influence of several maternal characteristics, initial intention, perceived social support, and breastfeeding knowledge. However, if research could be conducted with a larger sample, other potential factors such as infant characteristics, psychological condition, the influence of mass media, and previous breastfeeding experience could be included [12,[41][42][43]. Third, data were collected via participant recall and using a self-reported questionnaire that may be subject to recall bias and social desirability bias.…”
Section: Discussionmentioning
confidence: 99%